ASIAN HERMENEUTICS: NEW HORIZONS - Chackalackal, saju (Journal of Dharma, 2005)
Human beings are hermeneutic beings. Inasmuch as they are rational, they entail the capacity to understand and respond to whatever happens and whatever they encounter within the ever-expanding horizons of their lives. Understood literally as the capacity to interpret, being hermeneutic is a basic function of being human: basically, every human being involves in interpreting anything and everything that happens in and around him or her. In fact, it is the human way of understanding, appraisal, and appropriation.